Enhancing biomethane yield of coal in anaerobic digestion using iron/copper nanoparticles synthesized from corn straw extract. (1st July 2022) - Dong, Zhiwei; Guo, Hongyu; Zhang, Minglu; Xia, Daping; Yin, Xiangju; Lv, Jinghui
Highlights: Nanoparticles (NPs) synthesized from corn straw extract promote methane production. Iron NPs encourages the emergence of new liquid products. Iron NPs promote nutrient exchange between bacteria. Copper NPs inhibits the activity of acid-producing and CO2 /H2 -producing bacteria. Iron NPs increase the abundance of functional gene for producing more methane. Abstract: To investigate the influence of nanoparticles (NPs) as additives on methane production from coal, bituminous coal was selected for the biogas production experiment, and iron and copper NPs were synthesized by hydrothermal treatment of corn straw. Biomethane production, gas chromatography-mass spectrometry, microbial community structure, and functional gene expression were analyzed to determine the effect of NPs on coal conversion to biomethane. The optimal amount of iron NPs (Fe3 O4 ), composite NPs (Fe3 O4 /CuO), and copper NPs (CuO) for the biogas production experiment were 1.5 g/L, 1.0 g/L, and 1.5 g/L, respectively, and the corresponding methane production increased by 701.22%, 337.81%, and 12.20% compared to the biogas production experiment without NPs. After the addition of iron NPs, a new product (butylated hydroxytoluene) was produced, promoting fatty acid biosynthesis and decreasing the CO2 accumulation. The abundance of liquid products in the biogas production with composite NPs was not significantly different from the experimental group without NPs. The microbial community structure analysis results showed that adding NPs eliminated Lysinibacillus in the bacterial community, while Pseudomonas prevailed as the dominant bacteria. Copper NPs inhibited acid-producing and CO2 /H2 -producing bacteria ( Sphaerochaeta ). The abundance of functional genes involved in glycolysis and methane metabolism in the biogas production experiment with iron NPs was the largest, promoting biomethane production. Gene abundance related to nitrate reduction was the highest in experiments with copper NPs, while the gene abundance related to sulfate reduction was the same between copper and iron NPs groups.